2020
DOI: 10.1080/17439760.2020.1858333
|View full text |Cite
|
Sign up to set email alerts
|

The role of service-learning experiences in promoting flourishing among college-student youth mentors

Abstract: Service-learning experiences may uniquely promote flourishing (i.e. having meaning in life, social connections, and a positive outlook) for college students. To examine whether specific relational experiences within service-learning were associated with flourishing, we used data from a program where university students (N= 274; 21.2% first-generation) served as mentors to youth (ages 10-18) with prior exposure to adversity. We examined three experiences: opportunities to belong, supportive relationships, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 49 publications
1
4
0
1
Order By: Relevance
“…In line with most previous studies (50,77), our results provide additional evidence for the hypothesis that SL experience would have a positive impact on students' wellbeing. Meanwhile, students also showed significant improvement in MIL, which is in line with the limited available literature on the role of SL participation in students' construction of MIL (35,44,45). The present findings may be explained by the argument that SL participation allows students to achieve self-development, social commitment, and deep reflection on life experience, which are important sources of MIL (41,42).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In line with most previous studies (50,77), our results provide additional evidence for the hypothesis that SL experience would have a positive impact on students' wellbeing. Meanwhile, students also showed significant improvement in MIL, which is in line with the limited available literature on the role of SL participation in students' construction of MIL (35,44,45). The present findings may be explained by the argument that SL participation allows students to achieve self-development, social commitment, and deep reflection on life experience, which are important sources of MIL (41,42).…”
Section: Discussionsupporting
confidence: 88%
“…Another study showed that SL experience leads to changes in life meaning among student-teachers ( 44 ). Moreover, a recent study demonstrated that a sense of belonging and supportive relationships derived from the SL process predicted the development of MIL in students ( 45 ).…”
Section: Introductionmentioning
confidence: 99%
“…En este sentido, la propuesta se desarrolla con el alumnado de primer curso, porque resulta fundamental para ellos y ellas establecer contacto con los centros desde el inicio de su formación. En esta línea, existen estudios realizados con alumnado universitario de primer curso que demuestran que el ApS da un mayor sentido a su formación y les permite experimentar más interacciones sociales y desarrollar actitudes positivas hacia los demás (Maples et al, 2020).…”
Section: Discussionunclassified
“…Although the theory of change guided the evaluation of mentor outcomes, this study did not empirically test the links in the theory of change; therefore, it is not clear which of the evidence‐informed principles, processes and practices embedded in the Campus Connections Aotearoa service‐learning experience are the most important drivers of mentor outcomes. There is a growing process‐focused research base on the original Campus Connections model that continues to uncover important mediators and moderators of mentor and mentee outcomes (see Boat et al, 2019 and Maples et al, 2022 for examples). Ongoing review of this evidence will help to advance understanding of how to produce effective youth mentoring‐based service‐learning experiences for tertiary students and future research on Campus Connections Aotearoa's implementation could test process‐to‐outcome links to validate the Campus Connections Aotearoa theory of change for mentors.…”
Section: Discussionmentioning
confidence: 99%